P0172Clinical relevance of a pharmacogenetic approach using multiple transporter genes to predict response and resistance to imatinib therapy in Malaysian patients with chronic myeloid leukaemia. (July 2015) - Ankathil, Ravindran; Au, Anthony; Husin, Azlan; Baba, Abdul Aziz
Abstract : Background: Despite success with imatinib mesylate in patients with chronic myeloid leukaemia (CML), emergence of clinical resistance in 30% of patients treated with imatinib mesylate still remains a problem. Resistance could be due to a heterogenous array of mechanisms. Pharamcogenetic variability as a result of genetic polymorphisms in the imatinib mesylate transporter genes ABCB1, ABCG2, ABCC1, and ABCC2 could be potential determinants of variability in imatinib mesylate disposition and efficacy. This study investigated the association between ten polymorphisms of ABCB1 (1236 T>C, 2677G>T/A, 3435C>T), ABCG2 (34G>A, 421 C>A), ABCC1 (2012G>T, 2168G>A), and ABCC2 (−24C>T, 1249G>A, 3972 C>T) genes and response to imatinib mesylate with the ultimate aim of identifying putative genotypes and haplotypes associated with good response or resistance. Methods: Blood samples from 215 patients with CML (107 with a good response to imatinib mesylate and 108 who were resistant to imatinib mesylate) were genotyped for the 10 polymorphisms using PCR-RFLP. After determining the genotype and haplotype frequencies, their association with imatinib mesylate response was determined with odds ratio (OR). Findings: Resistance was significantly associated with patients who had homozygous ABCB1 1236CC genotype (OR 2.79, p  = 0.01). ABCG2 421AA genotype was associated with a good response (OR 0.29, p  = 0.01) while 421CC genotype was associated with imatinib mesylate resistance (OR 1.87, p  = 0.02). Haplotypes ABCB1 C1236 G2677 C3435 and ABCC2 T-24 G1249 T3972 were associated with imatinib mesylate resistance ( p  = 0.04 and p  = 0.03 respectively) while ABCG2 A34 A421 haplotype was associated with a good response to imatinib mesylate ( p  = 0.03). Interpretation: Genetic variation in these imatinib mesylate transporter genes might have consequences on mRNA stability, expression, protein folding degradation, intracellular localisation, substrate binding, and/or transporter kinetics and thus modulate variation in response. Pretreatment genotyping of these SNPs in patients with CML could be useful for predicting imatinib mesylate resistance which may allow the best choice of drug treatment for patients with CML.